Selective Curcuminoid Separation and Detection via Nickel Complexation and Adsorptive Stripping Voltammetry - Wray, D; Batchelor-McAuley, C; Compton, R (2012)
Curcumin is a widely studied biologically active redox molecule. Although sensitive, electrochemical methods are commonly hindered by their lack of specificity. This article demonstrates how curcumin may be readily separated from other structurally and electrochemically similar redox moieties. This separation is achieved through exploitation of the molecules diketone functionality providing a route for its selective chelation to nickel(II). Recovery of the curcumin from the nickel complex is achieved simply and quantitatively through acidification of the precipitate. Adsorptive stripping voltammetry at a carbon screen-printed electrode (SPE) is utilised both as a method for evidencing the effectiveness of the separation technique but further as a procedure for the analytical quantification of the curcumin concentration. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.